Occasionally Weakly Compatible Maps and Common Fixed Point Theorems in Certain New Generalized Symmetric Space - Abed, Abdalqadir Hamid; Al-Jumaili, Alaa. M. F. (Iraqi Journal of Science, 2024)
The major objective of the present paper is to study and investigate certain new class of generalized metric spaces namely, -symmetric spaces which is generalization of both -metric space and G-symmetric space. Moreover, employ the idea of the (E. A) property to establish the uniqueness of common fixed points of two pair of occasionally weakly compatible (OWC) maps under effect generalized contractive conditions in -symmetric spaces. Our main outcomes are generalization of various results of common fixed point theorems in the literature. In addition, we are equipping diverse convenient examples that support our major results.